HUKUM ISLAM DAN PEMBERDAYAAN EKONOMI UMAT - Masse, Rahman Ambo (DIKTUM: Jurnal Syariah dan Hukum, 2015)
Reactualization of Islamic law can be done through empowerment of fiqh and fatwa to understand that fiqh and fatwa are the product of scholars’ thought affected by the socio-cultural aspects accompanying it. The Product of that thought is used as a device to overcome the problems of the religious dimension of worship, muamalah, family law, civil and criminal. Generally, Muslims tend to assume that the product of fiqh thought is considered as religious because most of the practice and application of religious teachings are derived from fiqh, such as the ordinance of purification, prayer, fasting, pilgrimage, and etiquette for transaction which is appropriate to Shari’a guidance.